Raise Awareness on The Issues of Global Poverty: A Transdisciplinary Research in Human-Computer Interaction - Amin, Zaid; Zinaida, Rahma Santhi (UNIVERSITAS PAKUAN, 2024)
Global poverty is one of today's most pressing issues of sustainability. Raising global poverty awareness is critical, but incorporating Human-Computer Interaction (HCI) as a core to understanding how to design a technology that brings together both academia and stakeholders to see poverty eradicated is underutilized. Furthermore, several factors must be considered and more research is required, particularly when channeling awareness. This comprehension includes incorporating public interest, societal actors, human-centered ICT, and communication into a transdisciplinary investigation that can aid in the success of awareness-raising events. We then proposed to breaking down these major challenges into three study steps: co-design, co-production, and co-dissemination. The proposed transdisciplinary investigation combines philosophy of mind, human-oriented technology, and communication discipline. We proposed investigating and representing a collaboration framework to help generate more evidence of how incorporating Human-oriented ICT and communication discipline as well as understanding collaboration based on transdisciplinarity and integrated context of research concepts using a mix-methodology approach that combines an analysis of systematic literature review and meta-analysis approachment. More importantly, the study aims to stimulate systematic thinking and innovation in order to propose a paradigm for knowledge toward global sustainability, which will be designed and carried out in collaboration between academia and stakeholders, with this investigation focusing on the five paths out of poverty: access, opportunity, empowerment, security, and sustainability. This study challenges in transdisciplinary HCI should be paid attention to keeping design at the heart of HCI regardless of discipline boundaries being crossed, going even further in transdisciplinary HCI research and practice, and also studying the effects of transdisciplinarity in design from communication and collaboration perspectives, particularly with regard to global poverty eradication..